2019
DOI: 10.1007/s00403-019-01931-y
|View full text |Cite
|
Sign up to set email alerts
|

Narrowband UVB treatment induces expression of WNT7B, WNT10B and TCF7L2 in psoriasis skin

Abstract: WNT/β-catenin signaling pathways play a pivotal role in the human immune defense against infections and in chronic inflammatory conditions as psoriasis. Wnt gene alterations are linked to known comorbidities of psoriasis as obesity, diabetes and Crohn’s disease. The objective of this study was to investigate WNT7B, WNT10B, WNT16 and TCF7L2 gene and protein expression in lesional and non-lesional skin and in the peripheral blood of patients with chronic plaque psoriasis compared with healthy individuals. To inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…It remains to be confirmed if WNT10B has a similar effect in vivo, of protecting epidermis against NBUVB‐induced cellular senescence by preventing the cellular differentiation. Interestingly, in our data, WNT10B was higher in repigmented epidermis exposed long duration to NBUVB, and similarly, others found increased levels of WN10B in psoriatic epidermis after NBUVB treatment (Assarsson et al., 2019), possibly to prevent the NBUVB‐induced epidermal senescence, including the terminal differentiation of melanocytes.…”
Section: Discussionsupporting
confidence: 87%
“…It remains to be confirmed if WNT10B has a similar effect in vivo, of protecting epidermis against NBUVB‐induced cellular senescence by preventing the cellular differentiation. Interestingly, in our data, WNT10B was higher in repigmented epidermis exposed long duration to NBUVB, and similarly, others found increased levels of WN10B in psoriatic epidermis after NBUVB treatment (Assarsson et al., 2019), possibly to prevent the NBUVB‐induced epidermal senescence, including the terminal differentiation of melanocytes.…”
Section: Discussionsupporting
confidence: 87%
“…The primary mechanism of UV therapy was to promote the proliferation and differentiation of epidermal cells and melanocytes by up-regulation of the Wnt signaling pathway. 30 , 31 In addition, epithelial Wnt ligand secretion could promote hair follicle growth and regeneration. 25 In this study, the up-regulation of the Wnt signaling pathway was also observed after UV irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, numerous studies have shown that the therapeutic effect of drugs that are not direct activators or inhibitors of Wnt signalling pathway is also depend on the activity of Wnt signalling. 278 281 All above indicate that targeting Wnt signalling is an attractive strategy for the treatment of multiple diseases.…”
Section: Application Of the Wnt/β-catenin Pathway In The Clinicmentioning
confidence: 99%